Evolution of ZnO nanostructures as hexagonal disk: Implementation as photoanode material and efficiency enhancement in Al: ZnO based dye sensitized solar cells - Parra, Mohammad Ramzan; Pandey, Padmini; Siddiqui, Hafsa; Sudhakar, Vediappan; Krishnamoorthy, Kothandam; Haque, Fozia Z. (Applied Surface Science, 2019)
Hexagon shaped pristine and Al doped ZnO nanodisks (NDs) with exposed +/- [0001] polar facets were successfully synthesized using modified sol-gel method without the involvement of any structural directing or capping agents. It was investigated that OH- ions in mixed solvent system is responsible for pore formation and inhibit the growth of ZnO along the direction of c-axis leading to a high percentage exposure of active +/- [0001] polar facets and encourage the formation of ZnO NDs. Crystallographic analysis revealed that crystallite size and lattice constants are decreased, with the addition of Al3+ ions. The results obtained from Raman, and XPS analysis further corroborated with the XRD results, revealed the successful incorporation of Al3+ ions into ZnO lattice. Optical study revealed the band gap tunability with the incorporation of Al ion as dopant. Enhanced power conversion efficiency (PCE) of 1.96% (J(sc) similar to 7.69 +/- 0.23 mA/cm(2)) was observed for Al: ZnO hexagonal NDs based DSSC. The increased PCE in Al: ZnO based DSSC can be attributed to the higher inner surface area for dye anchoring by the interconnected network of the disk-like structure. The obtained results were satisfactory and most importantly the synthesis procedure proposed in present work is excellent for the synthesis of perfectly hexagonal shaped disks under precised synthesis parameters. The device interface study was further conducted using electrochemical impedance spectroscopy which revealed better charge transport process and charge storage ability with the incorporation of Al3+ ions into ZnO lattice.
Keywords: dye sensitized solar cells; Hexagonal disks; Sol-gel method; ZnO

Organic-inorganic perovskitoid with zwitterion cysteamine linker and its crystal-crystal transformation to ruddlesden-popper phase - Kour, Prachi; Reddy, Mallu Chenna; Pal, Shiv; Sidhik, Siraj; Das, Tisita; Pandey, Padmini; Mukherjee, Shatabdi Porel; Chakraborty, Sudip; Mohite, Aditya D.; Ogale, Satishchandra (Angewandte Chemie-International Edition, 2021)
We demonstrate synthesis of a new low-D hybrid perovskitoid (a perovskite-like hybrid halide structure, yellow crystals, P21/n space group) using zwitterion cysteamine (2-aminoethanethiol) linker, and its remarkable molecular diffusion-controlled crystal-to-crystal transformation to Ruddlesden-Popper phase (Red crystals, Pnma space group). Our stable intermediate perovskitoid distinctly differs from all previous reports by way of a unique staggered arrangement of holes in the puckered 2D configuration with a face-sharing connection between the corrugated-1D double chains. The PL intensity for the yellow phase is 5 orders higher as compared to the red phase and the corresponding average lifetime is also fairly long (143 ns). First principles DFT calculations conform very well with the experimental band gap data. We demonstrate applicability of the new perovskitoid yellow phase as an excellent active layer in a self-powered photodetector and for selective detection of Ni2+ via On-Off-On photoluminescence (PL) based on its composite with few-layer black phosphorous.
Keywords: Crystal growth; organic-inorganic hybrid composites; perovskite phases; photodetectors; zwitterions